2019
DOI: 10.1177/0886260519881530
|View full text |Cite
|
Sign up to set email alerts
|

Spousal Violence Against Women in India: A Social–Ecological Analysis Using Data From the National Family Health Survey 2015 to 2016

Abstract: Even after enactment of the Protection of Women From Domestic Violence Act 2005, over the last 10 years, the rate of decline of prevalence of spousal violence against women has remained low in India. This study attempts to explain the experience of spousal violence using a social–ecological framework. We analyzed the National Family Health Survey 2015 to 2016 (NFHS-4) data of 66,013 ever-married women aged 15 to 49 years. Participants in the domestic violence module of the NFHS-4 reported their experience of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 35 publications
7
48
5
1
Order By: Relevance
“…The odds of physical violence are greater for younger married women, with poorer socioeconomic position, and where underage marriage is common. 62 We found that 47% of women who had suffered violence had sought help from somebody. This is considerably more than the NFHS-4, which found that 14% of urban women who had experienced physical or sexual violence had sought help from any source, usually natal family, marital family, friend or neighbour.…”
Section: Discussionmentioning
confidence: 85%
“…The odds of physical violence are greater for younger married women, with poorer socioeconomic position, and where underage marriage is common. 62 We found that 47% of women who had suffered violence had sought help from somebody. This is considerably more than the NFHS-4, which found that 14% of urban women who had experienced physical or sexual violence had sought help from any source, usually natal family, marital family, friend or neighbour.…”
Section: Discussionmentioning
confidence: 85%
“…Women Characteristics (individual level predictors) associated with the prevalence of spousal violence of women were introduced in model-1 ( Table 4.2 ). Earlier study ( Ahmad et al, 2019 ) has shown that some degree of variation of women spousal violence could be explained by the individual level characteristics. Apart from this, model 0 ( Table 4.1 ) or unconditional model also confirmed to us that there has 20% variance of women spousal violence between states is at level-2 and rest of it at level-1.…”
Section: Resultsmentioning
confidence: 98%
“…Spousal violence mainly occurs in romantic relationships where one partner plays a dominant role and exerts his/her power over the others. Like other developing countries, in India spousal violence is still prevalent and about 33% ever-married women have ever experienced spousal physical, sexual or emotional violence from their current husband or most recent husband and 26% have experienced at least one in the 12 months preceding the survey ( Ahmad et al, 2019 ; International Institute for Population Sciences [ IIPS] & ICF, 2017 ). National Family Health Survey-4 (NFHS) also reported that 30% ever married women have experienced spousal physical violence where only 7% have experienced sexual violence and emotion violence only reported by 14% ever-married women in ever.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations